Nano Online 2016
DOI: 10.1515/nano.12951_2015.48
|View full text |Cite
|
Sign up to set email alerts
|

Self-illuminating quantum dots for non-invasive bioluminescence imaging of mammalian gametes

Abstract: Background: The fertility performance of animals is still a mystery and the full comprehension of mammalian gametes maturation and early embryonic development remains to be elucidated. The recent development in nanotechnology offers a new opportunity for real-time study of reproductive cells in their physiological environments. As a first step toward that goal, we evaluated the effectiveness of a fluorescent and luminescent nanoparticle for in vitro and ex vivo imaging of porcine gametes. Methods:Freshly harve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…These self-illuminating, inorganic nanoparticles are of interest to the field of theriogenology as they are biocompatible, photo-stable, and have a greater signal intensity than organic fluorescent molecules previously used to image gametes and other cell types in vivo [ 68 70 ]. Feugang et al [ 68 , 71 ] have demonstrated the real-time tracking ability of bioluminescent resonance energy transfer-conjugated quantum dot (BRET-QD) nanoparticles in vitro, in situ, and ex vivo using pig male gametes ( Sus scrofa domesticus ). Quantum dots can provide targeted or non-targeted imaging as a function of their size, emitted wavelengths, and conjugation possibilities [ 68 , 71 ].…”
Section: Reproductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These self-illuminating, inorganic nanoparticles are of interest to the field of theriogenology as they are biocompatible, photo-stable, and have a greater signal intensity than organic fluorescent molecules previously used to image gametes and other cell types in vivo [ 68 70 ]. Feugang et al [ 68 , 71 ] have demonstrated the real-time tracking ability of bioluminescent resonance energy transfer-conjugated quantum dot (BRET-QD) nanoparticles in vitro, in situ, and ex vivo using pig male gametes ( Sus scrofa domesticus ). Quantum dots can provide targeted or non-targeted imaging as a function of their size, emitted wavelengths, and conjugation possibilities [ 68 , 71 ].…”
Section: Reproductionmentioning
confidence: 99%
“…Feugang et al [ 68 , 71 ] have demonstrated the real-time tracking ability of bioluminescent resonance energy transfer-conjugated quantum dot (BRET-QD) nanoparticles in vitro, in situ, and ex vivo using pig male gametes ( Sus scrofa domesticus ). Quantum dots can provide targeted or non-targeted imaging as a function of their size, emitted wavelengths, and conjugation possibilities [ 68 , 71 ]. This engineered nano particle provides a new mean to visualize the molecular and cellular events during fertilization, in a similar way to fluorescent proteins, but at greater tissue depths [ 71 , 72 ].…”
Section: Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the complex did not hinder the movement of spermatozoa, it could be used for in vivo tracking of fertilisation success. This application also demonstrates the usefulness of QD technologies for deep tissue imaging of large animals, which is challenging with more traditional methods that are less specific and bright (Feugang et al, 2015). CdSe/ZnS QDs capped with dihydrolipoic acid (DHLA) were used to track a protein that regulates the cell cycle in African clawed frog (Xenopus laevis) embryos in vivo (Brandt et al, 2015).…”
Section: (C) Animalsmentioning
confidence: 99%
“…Streptavidin-conjugated CdSe/ZnS QDs injected into a zebrafish blastomere at the two-cell stage were transferred from mother to daughter cells through cell division via cytoplasmic bridges and exhibited bright fluorescence even in late developmental stages such as organogenesis (Rieger et al, 2005). A CdSe/ZnS QD complex involving a fluorescent dye, a cellpenetrating peptide and an antibody related to fertilisation regulation was utilised for tracking the movement of domestic pig (Sus scrofa domesticus) spermatozoa in female reproductive tracts (Feugang et al, 2015). The QD complexes specifically attached to male gametes, indicating that plasminogen is present in sperm cells.…”
Section: (C) Animalsmentioning
confidence: 99%